The determinants of food heritage based on age in Klang Valley, Malaysia / Adilah M.D Ramli... [et al.] - M.D Ramli, Adilah; Ahmad Sapawi, Dg Khairunisa; Mohd Zahari, Mohd Salehuddin (Universiti Teknologi MARA, Selangor, 2020)
Many countries have reported experiencing external pressures on their culture and tradition, which include losing their food heritage and identity. With that, Malaysia, as a multi-cultural country, is also giving greater concern in preserving its food heritage and identity. This paper empirically examined the public perception of food heritage determinants. Using Klang Valley as data collection setting, 676 respondents comprised of Malays, Chinese, Indian and others were surveyed. The collected data were analysed using the descriptive statistic, mean value and cross-tabulation analysis toward two age group (30-35 and >36 years old). Results revealed that in food heritage determinants which consisted of historical elements as well as practices and integration elements had presented positive perception with the majority of the respondents agreed on each attribute and were significantly different (p<0.05) between each age group. Few items under food characteristics and the value of uniqueness showed non-significant differences (p>0.05) when comparing the age group. This concludes that age group has impacted on some of the attributes which led to different opinion in regards to food heritage determinants.